How to support consumer-brand relationships: The role of corporate culture and human resource policies and practices. Issue 2 (7th April 2015) - Iglesias, Oriol; Saleem, Fathima Zahara
Abstract : Purpose: – The purpose of this paper is to identify the detailed human resource policies and practices that favor the expansion of consumer-brand relationships. Design/methodology/approach: – Due to the lack of studies in this specific field, this research leans toward adopting an exploratory and interpretative methodology. The data stems from 53 in-depth interviews spanning three case studies in the hotel industry. Findings: – The main contribution of this research is the identification and description of the human resource management (HRM) policies and practices which enable the development of consumer-brand relationships. The six policies and practices which this research considers key are: recruitment, promotion, training, communication, evaluation and compensation. Originality/value: – This is the first research that identifies and describes the HRM policies and practices which enable the development of consumer-brand relationships.